Internal Reformation Within the Contemporary Coptic Imagined Community: The Sunday School Movement and Mechanisms of Minority Survival - Adly, Mereet Hany (Journal of religious and theological information, 2019)
With the centennial jubilee of the Sunday School Movement (SSM) occurring in 2018, this article explores two main questions: what are the main features of the Coptic community as imagined by the leaders of the SSM? And what is the nature of the relationship between "Coptic" Christian and "national Egyptian" identities within the dominant discourse of the SSM? The article argues that the contemporary Coptic identity, as reconstituted by the SSM, helps the Coptic community to survive as a vertical ethnie. The new Coptic identity is rooted in and relies upon the exclusive use of demotic symbols and narratives. Thus equipped, modern Copts perceive themselves as part of an imagined spiritual community within the wider Egyptian community. Indeed, this article argues that the SSM's discourse presents a unique marble cake' model wherein religious and national identities are both present. By portraying Coptism as the area of interplay between Christianity and Egyptian-ness, the SSM blends "biological" and "cultural-ideological" modes of myth-making. Accordingly, to identify as Copt becomes equivalent to identifying as Egyptian.